How are NFT (Non-Fungible Token) transactions reviewed according to Islamic law? - Nur Rizqi Febriandika; Fadli Fadli; Denizar Abdurrahman Mi'raj (Borobudur Law Review, 2022)
In the current digitalization era, many people are motivated to increase economic income in many ways, one of which is using digital technology NFT (Non-Fungible Token). The use of technology contained in NFT has a positive impact on people who have expertise in digital art; this is used to significantly increase economic income. This study discusses the history of NFT, the mechanism of buying and selling NFT, the characteristics of NFT and the view of Islamic law on buying and selling NFT transactions. The purpose of this study is to find out what is meant by NFT, the history of NFT, characteristics of NFT, how the mechanism of NFT sales is, and to find out how Islamic law views NFT buying and selling transactions. This research is a type of qualitative research; the author uses a descriptive-analytical approach which is classified as a qualitative research type by searching through library data or library research. The results of this study found that the history of NFT began in the BC era (Before Cryptokittes) 2012-2016, Cryptokitties and Cyptopunks (2017-2021), and the Decentraland Era (Metaverse) (2021-present). The law of buying and selling NFT is not found in the Koran or Hadith specifically but can be studied based on the pillars and conditions of buying and selling that have been regulated in Islamic law. According to Islamic law, transactions in the sale and purchase of NFT are included in the permissible sale and purchase; the transaction of buying and selling NFT is considered valid as a form of buying and selling in Islam because of the terms and pillars of the sale and purchase have been fulfilled.